2020
DOI: 10.1016/j.chest.2020.08.1084
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Spontaneous Pneumothorax in Critically Ill Patients With Sars-Cov-2

Abstract: Spontaneous pneumothorax is a relatively common complication in critically ill patients with severe acute respiratory distress syndrome (ARDS). Limited data exists regarding pneumothorax in severe acute respiratory coronavirus 2 (SARS-CoV-2) patients. This study depicts cases of spontaneous pneumothorax in critically ill SARS-CoV-2 patients and explores the potential underlying mechanisms. METHODS: This is a retrospective cohort study of SARS-CoV-2 patients with severe ARDS admitted to a tertiary care center b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Since the data are collected based on administrative codes, it is not possible to establish whether a complication was present on admission or developed during the hospital stay. Rare complications of COVID-19 were not reported in this study [ 45 , 46 ]. Second, laboratory data and metrics like SOFA score, APACHE II, and SAPS III that have been validated to predict mortality in critically ill patients were not evaluated in our study [ 47 ].…”
Section: Discussionmentioning
confidence: 90%
“…Since the data are collected based on administrative codes, it is not possible to establish whether a complication was present on admission or developed during the hospital stay. Rare complications of COVID-19 were not reported in this study [ 45 , 46 ]. Second, laboratory data and metrics like SOFA score, APACHE II, and SAPS III that have been validated to predict mortality in critically ill patients were not evaluated in our study [ 47 ].…”
Section: Discussionmentioning
confidence: 90%
“…In a study 13 of 22 patients with confirmed SARS-CoV-2 infection on mechanical ventilation, 7 patients developed spontaneous pneumothorax. Chronic obstructive pulmonary disease was not present in any of the patients.…”
Section: Ventilator Setting Patient S Efforts As Other Possible Etiologies Of Air Leakmentioning
confidence: 99%
“…Median tidal volume (VT) was 6.1 mL/kg predicted body weight on day 1, and the value increased significantly up to day 7, positive end-expiratory pressure was 10 cmH2O (8)(9)(10)(11)(12) on day 1, with a slight but significant decrease to day 7. Ratio of partial pressure of arterial oxygen (PaO2) to fractional inspired oxygen (FiO2) was 160 [interquartile range (IQR) 111-218], respiratory system compliance 36 mL/cmH2O (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), driving pressure 12 cmH2O (10)(11)(12)(13)(14), and FiO2 0.60 (0•45-0•80) on day 1. Acute respiratory distress syndrome developed in 1672 (87.6%) of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Email:amahmoodpoor@yahoo.com patients exhibit mild symptoms and have a good prognosis, this disease may lead to life-threatening conditions. [5][6][7][8] Pneumothorax, tension pneumothorax, pneumomediastinum, pneumopericardium and subcutaneous emphysema are uncommon clinical manifestations in patients with COVID-19. These patients experience spontaneous pneumothorax more commonly (0.57%) than other critical patients.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The odds of developing spontaneous pneumothorax is 40 to 100 times higher in patients with COVID-19 compared to those without, and mechanical ventilation increases the risk of pneumothorax in COVID-19 patients. 5 , 6 According to a study, the pathophysiology of pneumomediastinum in COVID-19 patients can be explained by the Macklin effect. 7 The Macklin effect starts with alveolar rupture secondary to direct alveolar injury, leading to air leaking and dissection along the bronchovascular sheaths and eventually spreading of air within the mediastinum.…”
Section: Introductionmentioning
confidence: 99%